Penerapan Prinsip Desain Garden City Pada Perancangan Central Business District - Safitri Dewi Sufian; Yohannes Firzal; Mira Dharma Susilawati (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2019)
With its location in a strategic area of trade, economy, tourism and international industry, Batam City has to become a potential area to develop. For this reason, the city is targeted to be an industrial and trade city. The development of a new area such as the central business district (CBD) is an effort to increase this potential. Batam Central Business District is seen as a multifunctional economic area with residential and recreational facilities that is support by location in Batam Center. The design principles of the Garden City theory can be applied to this area. According to the theory, city development can environmentally and socially be oriented and supports the sustainability of a city and leads to the creation of a green city, apart from industrial development. The Garden City principles can be one of the foundations in developing Batam City's potential to become an economically and socially environmentally friendly region, while still paying attention to the arrangement of green areas, roads and building layouts based on the function of activities. The facilities in Batam CBD are divided into several zones such as commercial, residential, office, and recreation with the addition of public space into its design. Furthermore, by using the Garden City design principles, the design can make it easier for users to carry out activities and appear to be more developed and organized, while also adjusting to the environment and social, to attract the attention of investors in this city.